2021
DOI: 10.21203/rs.3.rs-1146656/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Entomological Indicators of Malaria Transmission Prior to a Cluster Randomised Controlled Trial of a “Lethal House Lure” Intervention in Central Côte D’Ivoire

Abstract: Background: A study was conducted prior to implementing a cluster randomised controlled trial (CRT) of a lethal house lure strategy in central Côte d’Ivoire and aimed to provide baseline information on malaria vectors in 40 village clusters. Methods: Human landing catches (HLC) was performed between November-December 2016, capturing mosquitoes indoor and outdoor between 18.00-08.00. Mosquitoes were processed for entomological indicators of malaria transmission (human biting rates, parity rates, sporozoite infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Interceptor G2) in Tanzania [49], soon in Benin [48,50], and the pilot deployments that are part of the New Nets Project led by PATH [51]. Furthermore, PermaNet ® Dual should be tested against wild populations of Anopheles funestus [32], or other main or secondary vectors of malaria in Africa [52][53][54][55][56]. Ultimately, in the present study, the series of hut and laboratory tests demonstrated that the chlorfenapyr component of PermaNet ® Dual could make a major contribution to controlling the pyrethroidresistant An.…”
Section: Discussionmentioning
confidence: 99%
“…Interceptor G2) in Tanzania [49], soon in Benin [48,50], and the pilot deployments that are part of the New Nets Project led by PATH [51]. Furthermore, PermaNet ® Dual should be tested against wild populations of Anopheles funestus [32], or other main or secondary vectors of malaria in Africa [52][53][54][55][56]. Ultimately, in the present study, the series of hut and laboratory tests demonstrated that the chlorfenapyr component of PermaNet ® Dual could make a major contribution to controlling the pyrethroidresistant An.…”
Section: Discussionmentioning
confidence: 99%